High-Sensitivity Refractive Index Sensing Based on Fano Resonances in a Photonic Crystal Cavity-Coupled Microring Resonator - Fangcao Peng; Zhuoran Wang; Guohui Yuan; Lei Guan; Zhenming Peng (IEEE Photonics Journal)
Aiming for high-sensitivity refractive index biosensing, we investigate Fano resonance in a one-dimensional photonic crystal cavity-coupled microring resonator (PCMRR) on a silicon chip. Calculated results show that utilizing the asymmetric line shape of the Fano resonance, the detection limit can be reduced by a factor of 5 and the intensity detection sensitivity of PCMRR can be increased by a factor of 5 compared with a regular silicon-on-insulator, reaching the values of ∼7.2 × 10−4 RIU and ∼1.76 × 104 dB/RIU, respectively. Owing to its simplicity, compact footprint, and excellent performances, our device would be a promising candidate for optical label-free sensing applications.